Porphyrins as Chiroptical Conformational Probes for Biomolecules - Gabriele Travagliante; Massimiliano Gaeta; Roberto Purrello; Alessandro D’Urso (Molecules)
Porphyrins are highly conjugated macrocyclic compounds that possess exceptional photophysical and chemical properties, progressively establishing themselves as versatile tools in the structural investigation of biomolecules. This review explores their role as chiroptical conformational probes, focusing on their interactions with DNA and RNA. The planar electron rich structure of porphyrin macrocycle that promote π–π interactions, their easy functionalization at the meso positions, and their capacity to coordinate metal ions enable their use in probing nucleic acid structures with high sensitivity. Emphasis is placed on their induced circular dichroism (ICD) signals in the Soret region, which provide precise diagnostic insights into binding mechanisms and molecular interactions. The review examines the interactions of porphyrins with various DNA structures, including B-, Z-, and A-DNA, single-stranded DNA, and G-quadruplex DNA, as well as less common structures like I-motif and E-motif DNA. The last part highlights recent advancements in the use of porphyrins to probe RNA structures, emphasizing binding behaviors and chiroptical signals observed with RNA G-quadruplexes, as well as the challenges in interpreting ICD signals with other RNA motifs due to their inherent structural complexity.